Characterization of diagnosed leukemia in pediatric patients aged 5 to 10 years in a E.S.E in Colombia (Cuidado y Ocupación Humana, 2024)
Leukemia is a malignant disease that frequently affects the pediatric population, characterized by alterations in the blood, bone marrow, and lymphatic system, and it represents one of the leading causes of childhood mortality. With the purpose of contributing to the understanding of this problem, a study was conducted to characterize the types of leukemia diagnosed in pediatric patients between 5 and 10 years old, treated at the Erasmo Meoz University Hospital in the city of Cúcuta during the years 2021 to 2023, considering risk factors and prevalence in this population. The study followed a quantitative, descriptive, retrospective, and cross- sectional approach, with a non-probabilistic sample determined by previously established inclusion and exclusion criteria. Clinical and sociodemographic variables were included, such as age, weight, height, place of origin, socioeconomic status, and health insurance coverage, as well as correlations between age, type of leukemia, and clinical outcome. The findings showed that the most frequent type was acute lymphoblastic leukemia, followed by acute myeloid leukemia, with no records of chronic leukemias. The most relevant risk factors were associated with family history, genetic disorders, and exposure to viral agents. The prevalence in this group corresponded to 0.29%, with most patients being foreigners, mainly from Venezuela, which highlights the influence of the border dynamics on hospital access and care. This research underscores the need to strengthen epidemiological characterization in order to guide preventive measures and timely healthcare interventions.
Keywords: Acute lymphoblastic leukemia; acute myeloid leukemia; prevalence; leukocytosis; hyperleukocytosis